Redefinisi Ketertiban Umum dari Kontrol Aparat Menuju Ketenteraman yang Berpihak pada Kesejahteraan Psikologis Masyarakat - Rizma Afian Azhiim; Gema Ramadhan Bastari (Jurnal Keamanan Nasional, 2025)
Law No. 23/2014 mandates public order and ‘ketenteraman’ (Trantibum) as a basic service but critically fails to provide an operational definition. This absence creates a fundamental legal gap, resulting in regulatory confusion, arbitrary enforcement, and significant human rights risks. Academic discourse mirrors this failure by focusing on the technical implementation by apparatuses like Satpol PP, rather than the conceptual void. This effectively normalizes discretionary power and equates Trantibum with social control. This study aims to fill this gap by reconstructing the meaning of Trantibum. Using a qualitative method with discourse analysis on regulations and scientific literature, the study presents key findings. First, the 'public' dimension of Trantibum refers to a governance dimension that necessitates accountability, transparency, and the rule of law. Second, 'public order' operates through two power relations: necessary standardization and high-risk securitization, which treats issues as security threats. Third, 'tranquility' is a subjective state of psychological well-being reconstructed through tranquility (democratic public space), composure (collective balance against threats), and serenity (religious freedom). The study concludes that realizing Trantibum as a basic service requires a paradigm shift from apparatus-centered control toward safeguarding democratic values, promoting a positive security discourse, and protecting religious freedom, in line with the principles of human security, which place individual well-being at the center of national security.